Construction of an expression vector for Lactococcus lactis based on an indigenous cryptic plasmid - Hooi, Wei Yeng; Shamsudin, Mariana Nor; Abdul Rahim, Raha (Academic Journals, 2009)
To construct an expression vector for Lactococcus lactis, the EmPMT fragment which contained the erythromycin resistance gene, P32 promoter, multiple cloning site (MCS) and terminator (T) was subcloned into the small cryptic plasmid pAR141. The resulting vector, designated as pAR1411, was found to be stably maintained in L. lactis MG1363 after transformation for at least 100 generations under non-selective conditions. The vector was also demonstrated to be able to express the gene coding for chloramphenicol acetyltransferase (cat) in L. lactis.